2019
DOI: 10.1242/dev.174888
|View full text |Cite
|
Sign up to set email alerts
|

The molecular anatomy of mammalian upper lip and primary palate fusion at single cell resolution

Abstract: The mammalian lip and primary palate form when coordinated growth and morphogenesis bring the nasal and maxillary processes into contact, and the epithelia co-mingle, remodel and clear from the fusion site to allow mesenchyme continuity. Although several genes required for fusion have been identified, an integrated molecular and cellular description of the overall process is lacking. Here, we employ single cell RNA sequencing of the developing mouse face to identify ectodermal, mesenchymal and endothelial popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 90 publications
(92 reference statements)
4
73
0
2
Order By: Relevance
“…Although the GSEA results are promising, the significant terms represent very general problems with development. To get a more specific view of the impact of genes with DNMs in craniofacial development, we used recently published single-cell RNA sequencing data from the lambdoidal junction of the developing murine upper lip 22 . The lambdoid junction is the point of fusion of three facial prominences creating the primary palate and upper lip, so we hypothesized that the marker genes for each cell cluster are among the best candidate genes in the genome to be involved in OFCs and could potentially harbor an excess of DNMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the GSEA results are promising, the significant terms represent very general problems with development. To get a more specific view of the impact of genes with DNMs in craniofacial development, we used recently published single-cell RNA sequencing data from the lambdoidal junction of the developing murine upper lip 22 . The lambdoid junction is the point of fusion of three facial prominences creating the primary palate and upper lip, so we hypothesized that the marker genes for each cell cluster are among the best candidate genes in the genome to be involved in OFCs and could potentially harbor an excess of DNMs.…”
Section: Resultsmentioning
confidence: 99%
“…To address this question, marker genes belonging to eight clusters of ectodermal cells and nine clusters of mesenchymal cells were analyzed ( Figure 2). The marker genes from two ectodermal cell clusters (E5/E10 and E0/E11) positioned at the nasal process fusion zone and the olfactory epithelium had a significant excess of protein-altering DNMs (Figure 2A Figure 2D) 22 . Overall these analyses point to genes expressed in the cells at the point of fusion as being particularly relevant for risk of developing an OFC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent single cell-seq analysis of murine embryonic faces reported a cluster of 248 genes co-expressed with the canonical periderm marker Krt17 43 . Genes associated with the top-scoring 0.1% bin of tiles are enriched for those that are expressed in mouse periderm (hypergeometric p-value = 0.044) 43 . Similarly, the zebrafish orthologs of such genes are expressed, on average, at higher levels in GFP-positive versus GFPnegative cells described above (Wilcoxon rank sum test, p-value = 8.371e-06).…”
Section: Zebrafish Periderm Enhancers Share a Binding Site Code With mentioning
confidence: 99%
“…Similarly, the zebrafish orthologs of such genes are expressed, on average, at higher levels in GFP-positive versus GFPnegative cells described above (Wilcoxon rank sum test, p-value = 8.371e-06). Finally, we analyzed tiles of the mouse genome using the classifier trained on zGPAEs and found that tiles in the topscoring 0.1% bin were strongly associated with genes expressed in mouse oral periderm (Fisher's Exact test, p = 2.2e-16) 43 . These findings suggest periderm enhancers in zebrafish, human and mouse genomes are enriched for the same transcription factor binding sites.…”
Section: Zebrafish Periderm Enhancers Share a Binding Site Code With mentioning
confidence: 99%